-12u+7=-1

Simple and best practice solution for -12u+7=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12u+7=-1 equation:


Simplifying
-12u + 7 = -1

Reorder the terms:
7 + -12u = -1

Solving
7 + -12u = -1

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -12u = -1 + -7

Combine like terms: 7 + -7 = 0
0 + -12u = -1 + -7
-12u = -1 + -7

Combine like terms: -1 + -7 = -8
-12u = -8

Divide each side by '-12'.
u = 0.6666666667

Simplifying
u = 0.6666666667

See similar equations:

| 3x^2-7x+3=2x^2-4x+3 | | j-3=7+6j | | 16/1 | | y^2-2xy+3=0 | | 7p-10=6p | | 5/50=t/4 | | 56y+5=13 | | 5/75=t/10 | | P/8=-51/24 | | 3/2=n/10 | | -14+49v=42 | | x^2=-54-15x | | 5/x=55/22 | | .5(8x-43+10)=2x | | 36+16u=52 | | -3(5z-12)= | | -x+179=229 | | 2/3(5x) | | 18x-3=20x-16 | | f(-7)=3y-5 | | 4(x+8)+x=12 | | f(y)=3y-5 | | 10x+20=2x-4 | | (4x-8)/(3)=4 | | 221=8-x | | 21+49x=7 | | 150(x/6) | | 268-w=148 | | 4x-(9x+8)=27 | | 6=6(4q+1) | | h(t)=t^2-3t+5.5 | | 36v+24=48 |

Equations solver categories